THE INFLUENCE OF URBANIZATION ON FORMING THE SOCIAL STRUCTURE OF AZERBAIJAN SOCIETY - RUMIANTSEV, Sergei (CENTRAL ASIA AND THE CAUCASUS, 2004)
The past two hundred years in Azerbaijan’s history has been a time of rapid, qualitative, and often dramatic change. It seemed a contemporary, dynamically developing society with a clearly marked social structure was about to appear, with a strong and large middle class at its center. But the first years of the 21st century, which was emotionally perceived as a kind of special watershed, have passed and talk about the need to create a developed civil society and reinforce the middle class are continuing without bringing about any perceptible changes. But it should be noted that if some researchers evaluate the events of the past years as positive and believe a middle class, which is so important and necessary to us, has just about been formed, others severely criticize the reforms of the 1990s, often calling them not only a waste of time, but also an obstacle hindering the country’s development. We would like to offer our own analysis of the situation in the republic, while in no way claiming the absolute truth of our conclusions. We begin our analysis with urbanization, a process that is playing a vital role in differentiating the social structure of both the residents in a particular country, and the planet’s population as a whole. In so doing, we will note straight away that this process should be viewed in terms of globalization of the economy, which became possible by creating up-to-date communication technology and an integrated financial space. The urbanization process is the result of globalization, on the one hand, and its most important “agent” on the other, without the mass dimensions of which it would be impossible to talk about building a post-industrial society.